EPIDEMIOLOGY OF EPISODIC ABUSE IN ALCOHOL DEPENDENCE WITH THE INFLUENCE HELIOGEOPHYSICAL FACTORS - Borisenko, V.V. (World of Medicine and Biology, 2014)
This paper presents the results of a study of archival materials 25169 inpatients with alcohol dependence (F10.2 - F10.4) Poltava Regional Clinical Psychiatric Hospital named after AF Maltsev odynadtsyatylitniy one full solar cycle from 1997 to 2007. The data on the incidence of alcohol drinking bouts in a long time , one of the region have shown that a complex psychobiological process. The number of hospitalized patients with episodic binge with alcohol dependence has increased in recent years . These epidemiological data suggest an association between the occurrence of occasional drinking bouts and tsyrkannualnymy rhythms that cause the clinical manifestations of these conditions and flyuktuatsyyu income patients for hospital treatment in a particular season. Disease onset correlated with peaks in solar activity and seasonal (usually spring and autumn ). The most pronounced peaks income patients with episodic alcoholic binge in March- May, less pronounced rise in October- December. Therefore, health care and therapeutic measures for patients with the disease under study should be performed in February- March and September- October.